Is CT-Based Perfusion and Collateral Imaging Sensitive to Time Since Stroke Onset? - Agarwal, Smriti; Matys, Tomasz; Marrapu, S. Tulasi; Scoffings, Daniel J.; Mitchell, Jennifer; Jones, P. Simon; Baron, Jean-Claude; Warburton, Elizabeth A. (Frontiers in Neurology, 2015)
Abstract Purpose CT-based perfusion and collateral imaging is increasingly used in the assessment of patients with acute stroke. Time of stroke onset is a critical factor in determining eligibility for and benefit from thrombolysis. Animal studies predict that the volume of ischemic penumbra decreases with time. Here we evaluate if CT is able to detect a relationship between perfusion or collateral status, as assessed by CT and time since stroke onset. Materials and Methods We studied fifty-three consecutive patients with proximal vessel occlusions, mean (SD) age of 71.3 (14.9) years at a mean (SD) of 125.2 (55.3) minutes from onset, using whole-brain CT perfusion (CTp) imaging. Penumbra was defined using voxel-based thresholds for cerebral blood flow (CBF) and mean transit time (MTT); core was defined by cerebral blood volume (CBV). Normalized penumbra fraction was calculated as Penumbra volume /(Penumbra volume +Core volume) for both CBF and MTT (PenCBF and PenMTT, respectively). Collaterals were assessed on CT angiography (CTA). CTp ASPECTS score was applied visually, lower scores indicating larger lesions. ASPECTS ratios were calculated corresponding to penumbra fractions. Results Both PenCBF and PenMTT showed decremental trends with increasing time since onset (Kendall’s tau-b=-0.196, p=0.055, and -0.187, p=0.068, respectively). The CBF/CBV ASPECTS ratio, which showed a relationship to PenCBF (Kendall’s tau-b=0.190, p=0.070), decreased with increasing time since onset (Kendall’s tau-b=-0.265, p=0.006). Collateral response did not relate to time (Kendall’s tau-b=-0.039, p=0.724). Conclusion Even within 4.5hrs since stroke onset, a decremental relationship between penumbra and time, but not between collateral status and time, may be detected using perfusion CT imaging. The trends that we demonstrate merit evaluation in larger datasets to confirm our results, which may have potential wider applications e.g. in the setting of strokes of unknown onset time.